Bubble Network System and Achievement Motivation Toward Students’ Writing Achievement - Lalu Suparman (PALAPA, 2016)
The investigated of this study was the effect of BNS (Bubble Network System ) strategy and achievement motivation toward students writing achievement at the eleventh graders of Madrasah Aliyah NW Kotaraja. The design of the research was post-test only control group design. The study involved 80 students as samples which were taken by using random sampling technique, where the sample were divided into two groups, experimental and control group. The collection of the data were collected using questionnaire and test, which were analyzed using two-ways ANOVA. The finding data of the study displayed that (1) there is a significant difference on the English writing between the students taught by using BNS strategy and conventional strategy (FA=33.5, p<0.05), (2) there is a significant interaction between teaching strategy and achievement motivation on the English writing (FAB =30.12, p<0.05), (3) for the students with high achievement motivation, there is a significant difference on the English writing taught by BNS strategy and conventional strategy (Qob = 10.4, p<0.05), (4) for the students with low achievement motivation, there is no significant difference on the English writing taught by BNS strategy and conventional strategy (Qob = 0.302, p > 0.05)